Development of Smart Context-Aware Services for Cargo Transportation An Operational Management Approach - Dzemydienė, Dalė; Burinskienė, Aurelija; Čižiūnienė, Kristina; Miliauskas, Arūnas (International Series in Operations Research & Management Science, 2022)
XIX, 418 p. 76 illus.